Spatial Statistics with S-Plus - Krahnke, Tillmann (Universitätsbibliothek Dortmund, 1999)
An overview is given over the S-Plus libraries and modules for statistical analysis of spatial data that are currently available at the Department of Statistics, University of Dortmund. It is believed that this includes all libraries currently available on the internet. Listings of functions show what statistical techniques are implemented, and where to find them. This facilitates the search for any particular function, and saves from re-programming of techniques that are already available. This overview may therefore also be viewed as a starting point for developing further analysis tools for spatial and spatio-temporal statistics in S-Plus.
Available Libraries and Functions
Keywords: geostatistics; lattice data; modules; public libraries; spatial point pattern; spatial statistics; s-plus; 310